Analysis of the Effect of Merit System Implementation in Realizing Sustainable Development in Malang City - Ariyanto, Wahyu; Riniwati, Harsuko; Wahyudi, Setyo Tri; Wardana, Fitri Candra (Wacana Journal of Social and Humanity Studies, 2025)
Today, the goal of sustainable development is a global problem all countries face.  Economic development does not pay attention to the environmental impacts, causing problems that occur today and risk future generations' survival.  Governments in each country are expected to participate actively in achieving sustainable development goals. On the other hand, governments also face problems of poor performance, corruption, collusion, nepotism, and slow public services.  Introducing a merit system is expected to improve the existing system of government. This article discusses the effect of implementing a merit system in realizing sustainable development. This research is located in the city of Malang. The sample comes from the State Civil Apparatus of Malang City Government consisting of structural officials, functional officials, and executive officials, with the Structural Equation Modeling Partial Least Square (SEM PLS) analysis method. Results showed that applying the merit system in recruitment and replacement, including mutation and promotion, significantly affects sustainable development. Keywords: recruitment, replacement, regional apparatus performance, sustainable development